Determinan Risiko Terjadinya Bayi Berat Lahir Rendah - Srimiyati Srimiyati; Keristina Ajul (Journal of Telenursing (JOTING), 2021)
This study aims to prove the risk factors for the mother, fetus and the environment on low birth weight babies (LBW). The research method used a cross-sectional design with a sample size of 1,489 LBW infants. The data analyzed were secondary data taken from the medical records of mothers who gave birth to live babies from January 2015 to December 2017. Data analysis used the chi-square test followed by logistic regression with the backward method. The results showed that what was proven to affect the incidence of LBW was the age of pregnant women at risk (OR: 1.382 CI: 1.052–1.815), gestational age (OR: 2.097; CI: 1.668–2.637), mother's occupation (OR: 0.347; CI: 0.276 –0.436), pregnancy complications (OR: 4,407; CI: 3,344–5,809), and sex of the baby (OR: 0.742; CI: 0.607–0.956). The cause of LBW was dominated by pregnancy complications (p=0.000) and gestational age (p=0.022). In conclusion, the risk factors for pregnancy with complications and gestational age are the most influential risk factors for low birth weight babies. Keywords: LBW, Pregnancy, Complications